A study on how evolution simulator utilizes the windows operating system to demonstrate artificial intelligence learning - Guillermo, Daniel Lester C. (Animo Repository, 2019)
This paper aims to discuss the integration of the following concepts: Artificial intelligence, evolution, and algorithms to produce simulations, specifically with the program "Evolution Simulator". Also including the application of the "Evolutionary Algorithm", Artificial Neural Networks, and probability in executing a virtually accurate evolution simulator. The effect of a computation-heavy program on hardware will also be expounded on as this program relies almost only on the system's CPU. To observe machine learning using the Windows operating system, the program "Evolution Simulator" is installed and executed. Tools from the program such as the joint, bones and muscle tools were utilized to create a model that would be used to run 100 generations with 25 population for 5 seconds each to reach the furthest distance. Results of the simulation show that within these trials, the program was able to learn the most efficient combinations of movement to reach the maximum distance. Hence, the program has demonstrated simple artificial intelligence learning using the Windows operating system. © 2019, World Academy of Research in Science and Engineering. All rights reserved.